Dexmedetomidine administration is associated with a reduced risk of ICU mortality in critically ill patients with ischemic stroke - Shuiyun Chen; Shujiang Ren; Xing Li; Kewei Liu (Frontiers in Neurology)
BackgroundAlthough the administration of dexmedetomidine (DEX) in intensive care unit (ICU) is rapidly increasing, its potential impact on critically ill patients with ischemic stroke has not yet been explored.MethodsPatient data were extracted from the Medical Information Mart for Intensive Care IV (MIMIC-IV 3.0) database to identify patients who received DEX and those who did not. The primary outcome was ICU mortality. Statistical analyses included multivariate Cox proportional hazards regression, propensity score matching (PSM), and inverse probability of treatment weighting (IPTW) to ensure the robustness of the findings.ResultsThis study included 646 patients (22.8%) with ischemic stroke who received DEX treatment, and 2,182 patients who did not receive DEX in the ICU. A significant reduction in ICU mortality was observed in the DEX group compared to the non-DEX group, with an adjusted hazard ratio (HR) of 0.52 [95% confidence interval (CI) 0.40–0.68, p < 0.001]. Within the matched cohort, DEX administration did not show a statistically significant increased risk of bradycardia and improvement in 90-day mortality outcomes.ConclusionThese findings suggest that DEX administration may reduce ICU mortality in patients with IS.